DNA double-strand break repair pathway regulates PD-L1 expression in cancer cells. Issue 1 (December 2017) - Sato, Hiro; Niimi, Atsuko; Yasuhara, Takaaki; Permata, Tiara; Hagiwara, Yoshihiko; Isono, Mayu; Nuryadi, Endang; Sekine, Ryota; Oike, Takahiro; Kakoti, Sangeeta; Yoshimoto, Yuya; Held, Kathryn; et al.
Abstract Accumulating evidence suggests that exogenous cellular stress induces PD-L1 upregulation in cancer. A DNA double-strand break (DSB) is the most critical type of genotoxic stress, but the involvement of DSB repair in PD-L1 expression has not been investigated. Here we show that PD-L1 expression in cancer cells is upregulated in response to DSBs. This upregulation requires ATM/ATR/Chk1 kinases. Using an siRNA library targeting DSB repair genes, we discover that BRCA2 depletion enhances Chk1-dependent PD-L1 upregulation after X-rays or PARP inhibition. In addition, we show that Ku70/80 depletion substantially enhances PD-L1 upregulation after X-rays. The upregulation by Ku80 depletion requires Chk1 activation following DNA end-resection by Exonuclease 1. DSBs activate STAT1 and STAT3 signalling, and IRF1 is required for DSB-dependent PD-L1 upregulation. Thus, our findings reveal the involvement of DSB repair in PD-L1 expression and provide mechanistic insight into how PD-L1 expression is regulated after DSBs. PD-L1 is upregulated in many cancers due to exogenous cellular stress. Here the authors show that PD-L1 is upregulated in response to DNA double strand breaks via STAT and IRF1 signalling.